2018
DOI: 10.5539/jmbr.v8n1p95
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mycobacterium tuberculosis Infection in Suspected Patients in a Teaching Hospital in Northeastern Iran: A Cross-Sectional Study

Abstract: Background: Mycobacterium tuberculosis is an infectious agent responsible for major health problems and a large number of mortalities. The prevalence of Mycobacterium tuberculosis infection varies across countries. Knowing the infection prevalence can aid in improving public health and reduce the associated costs. The aim of this study was to determine the prevalence of tuberculosis (TB) infection in suspected cases in Mashhad, Iran.Methods: All the clinical specimens suspected of TB infection were sent to a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
0
1
Order By: Relevance
“…The result of a recent study revealed that the frequency of MTB among females (50.2%) was slightly higher than males (49.8%) with no statistical signi cance differences (P > 0.05 The overall prevalence of MTB and RR-MTB among participants was 6.1% and 9.1%, respectively. The frequency of MTB in the present study was slightly higher than that reported in Iran (5.5%) (13) and lower than the reported prevalence in Brazil (12.9%) and Ethiopia (7.9%), respectively (14,15). Methods of diagnosis may be responsible for the substantial difference.…”
Section: Risk Factors Associated With Mtb Infectioncontrasting
confidence: 82%
“…The result of a recent study revealed that the frequency of MTB among females (50.2%) was slightly higher than males (49.8%) with no statistical signi cance differences (P > 0.05 The overall prevalence of MTB and RR-MTB among participants was 6.1% and 9.1%, respectively. The frequency of MTB in the present study was slightly higher than that reported in Iran (5.5%) (13) and lower than the reported prevalence in Brazil (12.9%) and Ethiopia (7.9%), respectively (14,15). Methods of diagnosis may be responsible for the substantial difference.…”
Section: Risk Factors Associated With Mtb Infectioncontrasting
confidence: 82%